A atenção primária em saúde no itinerário terapêutico de gestantes e puérperas que vivem com HIV/AIDS - Oliveira, Raissa Bastos (2024)
Introduction: In the face of a chronic disease with no established cure, such as human immunodeficiency virus (HIV) infection, which affects thousands of people, including women in the reproductive age group, understanding the therapeutic itineraries (TI) of pregnant and postpartum women is essential for comprehensive health care. Objective: The general objective of this dissertation was to understand the TI of pregnant and postpartum women living with HIV/AIDS who are followed up at basic health units (UBS) in the metropolitan region of João Pessoa, Paraíba. Methods: The research occurred in two stages, one theoretical and one empirical. The first was theoretical, and it remained throughout the empirical stage, given the scope of building the theoretical basis of the study and granting epistemic maturity for the interpretation and analysis of empirical data. In addition to the bibliographic review included in the introductory chapter, a scientometric study was carried out to understand the state of scientific knowledge on the relationship between primary health care (PHC) and pregnant and postpartum women living with HIV/AIDS. The bibliometric analysis software VOSviewer® processed the metadata extracted from 279 articles published from 1987 to 2024 and registered it in the Scopus database. The primary study, a field study with a qualitative approach, investigated ten women, eight pregnant women and two postpartum women selected by snowball sampling. Data were collected from September 2023 to March 2024 through notes in a field diary, a questionnaire, and interviews according to a semi-structured script. The recorded and transcribed interviews were processed in the lexical analysis program IRaMuTQ® and, after the author's interpretation in confluence with the theoretical framework of the study, the results were presented and discussed in thematic categories. The research was approved by the Ethics Committee under opinion no. 6,302,421. Results: The scientometric study showed that interest in the role of PHC in the care of pregnant and postpartum women with HIV/AIDS is global and interdisciplinary, but more expressive in medicine (n=256). The United States is the most productive (n=118) and most cited (n=5,441). Brazil, with 16 studies, reached 150 citations. The publications investigated reflected mainly on pregnancy during adolescence, adherence to antiretroviral therapy, HIV/AIDS screening, breastfeeding, the risk of vertical transmission, prenatal care and the correlation between HIV and syphilis. The participants in the empirical research were between 20 and 39 years old, the majority declared themselves brown (n=6) and had rudimentary socioeconomic and educational levels. Six women had not even completed elementary school, and only one had a college degree. Six of them depended on government assistance programs. Five categories emerged from their oral testimonies: “family perspectives,” “religiosity,” “sexual and emotional relationships,” “diagnosis,” and “specificities of the therapeutic itinerary.” Conclusions: Pregnant and postpartum women diagnosed with HIV/AIDS may experience various forms of violence that undermine their human dignity, including restrictions within the family. Their main concerns are the well-being of their children, and one of their fears is the possibility of vertical transmission. The theoretical surveys corroborate the findings of the empirical study, elucidating that, in the IT of pregnant and postpartum women living with HIV/AIDS, several social determinants intersect and can hinder, or even fragment, the search for health care. In this context, it is up to health professionals to train themselves to provide comprehensive care, perceiving women as biopsychosocial beings.